PHB granules are attached to the nucleoid via PhaM in Ralstonia eutropha - Wahl Andreas (BMC Microbiology, 2012)
Abstract Background Poly(3-hydroxybutyrate) (PHB) granules are important storage compounds of carbon and energy in many prokaryotes which allow survival of the cells in the absence of suitable carbon sources. Formation and subcellular localization of PHB granules was previously assumed to occur randomly in the cytoplasm of PHB accumulating bacteria. However, contradictionary results on subcellular localization of PHB granules in Ralstonia eutropha were published, recently. Results Here, we provide evidence by transmission electron microscopy that PHB granules are localized in close contact to the nucleoid region in R. eutropha during growth on nutrient broth. Binding of PHB granules to the nucleoid is mediated by PhaM, a PHB granule associated protein with phasin-like properties that is also able to bind to DNA and to phasin PhaP5. Over-expression of PhaM resulted in formation of many small PHB granules that were always attached to the nucleoid region. In contrast, PHB granules of ∆phaM strains became very large and distribution of granules to daughter cells was impaired. Association of PHB granules to the nucleoid region was prevented by over-expression of PhaP5 and clusters of several PHB granules were mainly localized near the cell poles. Conclusion Subcellular localization of PHB granules is controlled in R. eutropha and depends on the presence and concentrations of at least two PHB granule associated proteins, PhaM and PhaP5.